2009
DOI: 10.1007/978-3-642-04636-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Personalisation of Learning in Virtual Learning Environments

Abstract: Abstract. Personalization of learning has become a prominent issue in the educational field, at various levels. This article elaborates a different view on personalisation than what usually occurs in this area. Its baseline is that personalisation occurs when learning turns out to become personal in the learner's mind. Through a literature survey, we analyze constitutive dimensions of this inner sense of personalisation. Here, we devote special attention to confronting learners with tracked information. Making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 34 publications
0
28
0
5
Order By: Relevance
“…The authors concluded that a hybrid combination of the user and system menus would be interesting future research. Verpoorten et al (2009), within a learning environment, also highlighted the support that user-initiated personalization provides for perceived controllability and self-efficacy.…”
Section: Personalizationmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors concluded that a hybrid combination of the user and system menus would be interesting future research. Verpoorten et al (2009), within a learning environment, also highlighted the support that user-initiated personalization provides for perceived controllability and self-efficacy.…”
Section: Personalizationmentioning
confidence: 98%
“…Park et al (2007), Verpoorten et al (2009) -has focussed on relatively static information environments, where the contextual inputs used for system-initiated personalization may vary between users, but are relatively static for a specific individual. Therefore although this work can highlight the potential benefits of different personalization approaches, it may have limited applicability to a highly dynamic environment such as a large sports event, where the focus of attention is away from a mobile device, and there are scheduled and unscheduled temporal tensions (Tamminen et al, 2004).…”
Section: Personalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In these initiatives a user might not decide which tools she is going to use and they will be limited to institutional decisions. Some initiatives in this scenario are: LMS defined for the integration of external tools [29], Google Wave Gadgets integrated into Moodle [30], PLE introducing tools based on log analysis [31], initiatives based on tools integration driven by learning design activities [32], integration architectures [33], etc. These initiatives have several problems such as: integration problems between tools, context integration difficulties and the customisation of student learning tools are constrained by the institution, etc.…”
Section: Research Contextmentioning
confidence: 99%
“…Students or learners, just like customers or product consumers, are also in need of personalized recommendations for learning resources and activities that will match-up with their personal needs, preferences, prior knowledge, and current situation to facilitate an individualized learning or to offer a more personalized learning environment that will promote learning outcomes (Drachsler, Hummel & Koper, 2007;Verpoorten, Glahn, Kravcik, Ternier & Specht, 2009). This need is especially true in subjects that require higher levels of analytical and logical thinking skills, such as computer programming.…”
Section: Introductionmentioning
confidence: 99%